Current Therapeutic Options in Type 2 Diabetes Mellitus: A Practical Approach - Sheehan, Michael T. (Marshfield Clinic Research Foundation, 2003)
The incidence of type 2 diabetes mellitus (DM) in the United States continues to grow rapidly, paralleling the overweight and obesity epidemic. For many years the only therapeutic options for type 2 DM were sulfonylureas and insulin. However, over the last 9 years there has been an explosion of new and exciting agents approved for the treatment of type 2 DM. Some of the treatments target insulin deficiency and others insulin resistance, the hallmarks of the disease. Other drugs delay the intestinal absorption of carbohydrate. Recently several combination agents have been released. With these new drugs has come an overwhelming mountain of information, making it difficult for the busy clinician to know how best to manage the ever-increasing portion of patients with type 2 DM. New questions have arisen: Which agent to start as first line? How much of this drug to use before adding something else? How long for this drug to reach full effect? Which agent to add second? Should a patient uncontrolled on dual therapy begin insulin or start a third oral agent? If insulin therapy is started, what should become of the patient's oral agents? How best to explain the patient's weight gain on therapy? These are not easy questions and no review can fully detail all the therapeutic combinations possible. Instead, the practical approach of reviewing the agents in terms of their mechanism of action and critically comparing their dosing, effect and cost, is undertaken herein. Also addressed is the possible niche some newer classes of agents and combination drugs may or may not hold in the management of type 2 DM. The decision of using insulin versus a third oral agent will be looked at from the standpoint of where the patient is on dual therapy in relation to the hemoglobin A(1c) goal. In this way it is hoped that some clarity will be brought to the dizzying array of information that both the physician and patient have to deal with in regard to the management of this prevalent and serious disease.